College communities abroad : Education, migration and Catholicism in early modern Europe - O'Connor, Thomas; Chambers, Liam (Book collections on Project MUSE., 2018)
This book repositions early modern Catholic abroad colleges in their interconnected regional, national and transnational contexts. From the sixteenth century, Irish, English and Scots Catholics founded more than fifty colleges in France, Flanders, Spain, Portugal, the Papal States and the Habsburg Empire. At the same time, Catholics in the Dutch Republic, the Scandinavian states and the Ottoman Empire faced comparable challenges and created similar institutions. Until their decline in the late-eighteenth century, tens of thousands of students passed through the colleges. Traditionally, these institutions were treated within limiting denominational and national contexts. This collection, at once building on and transcending inherited historiographies, explores the colleges' institutional interconnectivity and their interlocking roles as instruments of regional communities, dynastic interests and international Catholicism. --